2020
DOI: 10.1177/0047287520938869
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Agritourism Experiences on Consumer Behavior toward Local Food

Abstract: Agritourism—visiting a working farm for education or recreation—may serve as a tool to increase local food consumption as it often includes opportunities to purchase local food on-site. Yet, the influence of agritourism on consumers’ local food purchasing behavior remains underexplored. Thus, this study measures the impact of agritourism experiences on consumers’ intentions to purchase local food. To do so, visitors were surveyed at six agritourism farms with similar agritourism activities (e.g., U-pick, educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 73 publications
1
47
0
Order By: Relevance
“…The high relational social capital in terms of members' willingness to help and share professional knowledge and information with other members shows that the association effectively helps to build social ties, which in turn fosters trust, reciprocity, and cooperation among members [27,29,31,32]. The high cognitive social capital among members, indicating strong levels of shared values, attitudes, and beliefs towards their association, can facilitate collective action [26,28], which in the case of agritourism is to increase customers' awareness of the local food systems and producers [5]. Lowest levels of structural social capital found indicate that further measures are needed to build social connections and relationships at the personal level among members [25,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high relational social capital in terms of members' willingness to help and share professional knowledge and information with other members shows that the association effectively helps to build social ties, which in turn fosters trust, reciprocity, and cooperation among members [27,29,31,32]. The high cognitive social capital among members, indicating strong levels of shared values, attitudes, and beliefs towards their association, can facilitate collective action [26,28], which in the case of agritourism is to increase customers' awareness of the local food systems and producers [5]. Lowest levels of structural social capital found indicate that further measures are needed to build social connections and relationships at the personal level among members [25,44].…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of networks and use of SNA in tourism, although still novel and rare, has increased in recent years, either to examine overall networks within specific tourism activities (e.g., food tourism) or macro structures such as tourism governance and sustainable tourism [55,56]. Overall, the extant literature stresses the need of agritourism operators to establish and nurture social networks with customers as well as with other farmers to facilitate the exchange of knowledge and resources [5,9,56,57]. Developing social network ties within the community have a positive effect on microbusiness success of micro agritourism operations [53].…”
Section: Social Network: Concept and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a survey of 207 farms across North Carolina, Ferreira (2019) reported that the sales of farm experiences, tours, and stays to visitors were deemed at least very important by 45.4% of farmers, accounting for an estimated 14.4% of total farm income. Finally, agritourism offerings in the state may include a diverse set of educational, farm-based recreation, recreational self-harvest, hands-on, and other nonagricultural recreation (e.g., bounce castles, swings) activities (Brune, Knollenberg, Stevenson, Barbieri, & Schroeder-Moreno (2020).…”
Section: Tourism Microentrepreneurshipmentioning
confidence: 99%
“…In addition, renewed interest in food systems and local food has provided the opportunity for farmers to invite the general public to their farms, creating both educational and economic value (Chase & Gubinger, 2014;Martinez, 2010). More recent research suggests that agritourism supports local food systems and enhances direct-to-consumer sales not only by directly influencing tourists' purchasing behavior but also by more generally promoting a broader interest in agriculture (Brune et al, 2020).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%